A W-band switch-less Dicke receiver for millimeter-wave imaging in 65nm CMOS - Feng, Guangyin (2018)
This paper presents a switch-less direct-detection Dicke receiver for millimeter-wave imaging applications. A configurable dual-path LNA (CDP-LNA) with negative transformer feedback and inductive positive feedback is proposed to remove lossy switches in traditional Dicke receivers. Under a 1.8 V supply voltage, the CDP-LNA consumes 52.3 mW dc power and each path of the CDP-LNA achieves power gain of 26.8 dB, minimum NF of 6.4 dB, and 3-dB bandwidth of 25.5 GHz. Based on the inherent switching of the CDP-LNA, a switch-less Dicke receiver is implemented, eliminating the sensitivity degradation due to the insertion loss of Dicke switch. Fabricated in 65nm CMOS process, the prototype exhibits a 3-dB bandwidth of 11.5 GHz with centre frequency of 82.5 GHz, achieving a noise-equivalent power of 9.3 fW/Hz0.5 and a noise-equivalent temperature difference of 0.65 K with total power consumption of 52.6 mW.